Brief Mindfulness-Based Cognitive Therapy in Women With Myocardial Infarction - Tanya M. Spruill, PhD; Chorong Park, PhD, RN; Jolaade Kalinowski, EdD; Milla E. Arabadjian, PhD, RN; Yuhe Xia, MSc; Amanda J. Shallcross, ND, MPH; Pallavi Visvanathan, PhD; Nathaniel R. Smilowitz, MD, MS; Anaïs Hausvater, MD; Sripal Bangalore, MD, MHA; Hua Zhong, PhD; Ki Park, MD; et al. (JACC: Advances)
Background: Elevated perceived stress is associated with adverse outcomes following myocardial infarction (MI) and may account for poorer recovery among women vs men. Objectives: This randomized controlled trial tested effects of a mindfulness-based intervention on stress levels among women with MI. Methods: Women with elevated stress (Perceived Stress Scale [PSS-4]≥6) at least 2 months after MI were enrolled from 12 hospitals in the United States and Canada and via community advertising. Participants were randomized to a remotely delivered mindfulness intervention (MBCT-Brief) or heart disease education, both 8 weeks long. Follow-up was 6 months. Changes in stress (PSS-10; primary outcome) and secondary outcomes (depressive symptoms, anxiety, quality of life, disease-specific health status, actigraphy-assessed sleep) were compared between groups. Results: The sample included 130 women with MI (mean age 59.8 ± 12.8 years, 34% racial/ethnic minorities). In intention-to-treat analysis, PSS-10 scores declined in the MBCT-Brief arm (−0.52 [95% CI: −0.77 to −0.28]) but not the heart disease education arm (−0.19 [95% CI: −0.45 to 0.06]; group×time interaction P = 0.070). The effect was stronger in per-protocol analysis of participants who completed ≥4 intervention sessions (P = 0.049). There were no significant differences in secondary outcomes in intention-to-treat or per-protocol analyses. Within the MBCT-Brief arm, more frequent mindfulness practice was associated with greater reductions in stress (P = 0.007), depressive symptoms (P = 0.017), and anxiety (P = 0.036). Conclusions: MBCT-Brief was associated with greater 6-month reductions in stress than an active control among adherent participants. More frequent mindfulness practice was associated with greater improvements in psychological outcomes. Strategies to engage women with MI in mindfulness training and support regular home practice may enhance these effects.